KEMAMPUAN MENULIS RUPAMA SISWA KELAS VIII SMP NEGERI MANGARABOMBANG KABUPATEN TAKALAR - Syarifah Ramdana; M, Asia; Asri, Aswati (Journal Studies in Indonesian Language and Literature, 2024)
This study aims to describe the ability to write rupama of class VIII students of SMP Negeri 1 Mangarabombang, Takalar Regency. This type of research is quantitative research in the form of quantitative descriptive. The variable of this research is the ability to write rupama. The population in this study were all VIII grade students of SMP Negeri 1 Mangarabombang Takalar Regency, totalling 10 class groups. Meanwhile, the sample determined in this study were students of class VIII.A SMP Negeri 1 Mangarabombang Takalar Regency totalling 34 people, using simple random sampling technique. The data collection technique used is the written test technique. The data collected will be analysed using descriptive statistical techniques.The results showed that the ability to write rupama of class VIII students of SMP Negeri 1 Mangarabombang Takalar Regency was declared incapable. This can be seen in the percentage of students who scored ≥ 75 in the able category did not reach the set criteria of 75%, but only 61.8%.